2007
DOI: 10.1111/j.1439-0507.2007.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofCandidaon the tongue and intertriginous areas of psoriatic and atopic dermatitis patients

Abstract: SummaryData in the literature regarding the prevalence of Candida in psoriatic and atopic dermatitis patients are controversial. We conducted a prospective study to determine the prevalence of Candida on the tongue, axillae and groin of psoriatic patients when compared with atopic dermatitis patients and normal controls. During the period 2003-2005, data were collected from 100 psoriatic patients, 100 patients with atopic dermatitis and 100 normal controls. Fungal test specimens for Candida were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 11 publications
6
24
1
Order By: Relevance
“…This could be due to exclusion of smokers, patients with systemic disease, patients who use dentures, and patients taking immunosuppressive drugs. In the current study, Candida albicans was the only species isolated from the oral cavity, which is relatively consistent with the result of previous studies that introduced Candida albicans as the most common Candida species isolated from psoriatic patients . In the past two decades, a higher incidence of non‐albicans species has been reported, especially among immunosuppressed patients .…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to exclusion of smokers, patients with systemic disease, patients who use dentures, and patients taking immunosuppressive drugs. In the current study, Candida albicans was the only species isolated from the oral cavity, which is relatively consistent with the result of previous studies that introduced Candida albicans as the most common Candida species isolated from psoriatic patients . In the past two decades, a higher incidence of non‐albicans species has been reported, especially among immunosuppressed patients .…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed a significantly higher prevalence of Candida colonization in the oral cavity of patients with psoriasis compared with the control group. This result is incompatible with those of Leibovici et al . but is consistent with the findings of Waldman et al …”
Section: Discussionsupporting
confidence: 63%
“…can provoke psoriasis via the activation of complement system and neutrophil recruitment . By contrast with previous studies, we applied molecular methods in the identification of yeast species and thus identified a greater diversity of yeast species than in previous studies. In the present study, C. albicans was the most common species of Candida , both in the oral cavity and in the skin of patients with psoriasis, a finding that concords with those of other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors found no increase in the prevalence of Candida in intertriginous area of psoriatic patients as compared with healthy individuals (Flytstrom et al, 2003;Leibovici et al, 2008). As ketoconazole appeared to be helpful in the treatment of some inverse psoriasis patients, the authors suggested an anti-inflammatory effect, which may explain some of its beneficial effects irrespective of Candida infection.…”
Section: Fungal Superantigensmentioning
confidence: 94%